An epidemiological study on the prevalence of self-medication practises: a serious threat for the population in the Muvattupuzha region in Kerala, India - James, Anitta Merlin, Bharat Mishra, Jeeva Joseph, Sandramol Shaji, Jude (Journal of Experimental Sciences)
This study is an investigation on Self medication, defined as the ‘use of a product without medical prescription or consultation in order to prevent or treat a disease or a symptom or to promote health’. The main issues in self-medication are improper usage of resources, OTC abuse, pathogen resistance and potential side effects with prolonged suffering in many of the cases. A prospective, cross -sectional questionnaire based study was carried out among 450 people selected by random sampling in the Muvattupuzha, Kerala, region. The main objectives of this study were to find out the reason and type of illness for which people self-medicate, prevalence of self-medication during pregnancy, self-medication with antibiotics and pharmacist’s approach while dispensing the OTC drugs. In the study, it was clear that a majority of the population self-medicate which includes the prescription drugs and even antibiotics. Self-medication is a serious public health concern; the remedy is to provide health education and which is the responsibility of all the pharmacists.